The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3174/ajnr.a5167
|View full text |Cite
|
Sign up to set email alerts
|

Large Basilar Apex Aneurysms Treated with Flow-Diverter Stents

Abstract: Flow diversion is a feasible technique with an efficacy demonstrated at a midterm follow-up, especially in the case of basilar apex aneurysm recurrences after previous endovascular treatments. Concern about its safety profile still exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…However, as this location is less accessible for clipping, FDD can be an option for complex or recurrent aneurysms, although ischemic and hemorrhagic complications are a concern. 26 In a multicentric series of 16 complex basilar tip aneurysms, complete/near complete occlusion was achieved in 68.8% of cases, with higher rates in case of adjunctive coiling. One thromboembolic event and one delayed SAH occurred.…”
Section: Bifurcation Aneurysmsmentioning
confidence: 96%
“…However, as this location is less accessible for clipping, FDD can be an option for complex or recurrent aneurysms, although ischemic and hemorrhagic complications are a concern. 26 In a multicentric series of 16 complex basilar tip aneurysms, complete/near complete occlusion was achieved in 68.8% of cases, with higher rates in case of adjunctive coiling. One thromboembolic event and one delayed SAH occurred.…”
Section: Bifurcation Aneurysmsmentioning
confidence: 96%
“…The mean time to complete occlusion overall confirmed by the first imaging was 10.0 ± 1.1 months (range, 4. [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The mean time to complete occlusion confirmed by the first imaging was significantly longer in fusiform aneurysms than saccular aneurysms (12.1 ± 3.9 months vs. 7.1 ± 3.5 months; p = 0.036).…”
Section: Angiographic Outcomesmentioning
confidence: 99%
“…Although DAPT is recommended before SACE to prevent ischemic complications, Hudson reported that shunting with DAPT increased postoperative cerebral hemorrhage. [7] Given the existence of a case report of successful flow diverter use for the treatment of a basilar aneurysm, [2] we aimed to achieve permanent cure by placing a FRED for flow diverter or an LVIS stent in expectation of an FD effect with DAPT after the first coil embolization [Table 2]. SAPT was started before the first coil embolization, and DAPT before the second cerebral endovascular treatment was administered over 10 days after the shunt operation.…”
Section: Discussionmentioning
confidence: 99%